Publication Bias and Editorial Statement on Negative Findings - Cristina Blanco-Perez; Abel Brodeur (Institute of Labor Economics (IZA), 2019)
In February 2015, the editors of eight health economics journals sent out an editorial statement which aims to reduce the extent of specification searching and reminds referees to accept studies that: "have potential scientific and publication merit regardless of whether such studies' empirical findings do or do not reject null hypotheses". Guided by a pre-analysis, we test whether the editorial statement decreased the extent of publication bias. Our differences-in-differences estimates suggest that the statement decreased the proportion of tests rejecting the null hypothesis by 18 percentage points. Our findings suggest that incentives may be aligned to promote more transparent research.
Keywords: A11; C13; C44; I10; 330; research in economics; pre-analysis plan; specification searching; publication bias; incentives to publish